Factors associated with work and taking prescribed methadone or buprenorphine among Swedish opiate addicts. (April 2015) - Blom Nilsson, Marcus; Chassler, Deborah; Lundgren, Lena M.
Highlights: Predisposing, enabling and need factors associated with and work/use of medications. Parental status associated with work and use of medications for opiate dependence. Psychiatric medication use associated with use of medication for opiate dependence. Abstract: Background/aims: Using national register data from 2002 to 2008, this exploratory study examines for opiate addicts ( n = 2638) whether there is an association between predisposing, enabling and need factors and working and taking methadone or buprenorphine prescribed by a physician for a year or more. Methods: Chi-square analyses and One-way ANOVA were used to determine significant relationships between the independent variables and the dependent variable. A binomial logistic regression model, with variables entered as a single block, measured statistical associations between the independent variables and the dichotomous dependent variable. Results: Men and those with greater number of years of education (7%) and those with children were 7.08 times more likely to be working and taking prescription methadone or buprenorphine. Those who had more inpatient drug treatment episodes (5%), those who had been charged with crime 3.23 times, and those who had used psychiatric medications were 8.43 times more likely to be working and to have taken prescription methadone or buprenorphine one year or more. Conclusion: This study highlights that clients in treatment for opiate addiction who are working and have received methadone or buprenorphine treatment may have better treatment retention and be more integrated socially than their counterparts even though they have a higher level of problem severity and treatment needs.